Samples of Turkey in the Best Tourism Village (Zien Journal of Social Sciences and Humanities, 2022)
Rural tourism is a type of tourism for the use of rural areas in the country for touristic purposes. Natural resources in rural areas have a remarkable feature for both tourists and tourism establishments. Encouraging tourism entrepreneurship, especially in areas with underdeveloped and small businesses, contributes to the realization of development in rural areas. The importance of rural tourism has been recognized in many countries around the world and studies have begun on this subject. The World Tourism Organization has launched the best tourism villages initiative for tourism development in rural areas. In 2021, Mustafapasa village of Nevsehir and Taraklı district from Sakarya received the best tourism villages initiative award from Turkey. In this study, the best tourism villages initiative Mustafapasa and Taraklı are examined within the scope of rural tourism